2018
DOI: 10.3126/hprospect.v11i0.7420
|View full text |Cite
|
Sign up to set email alerts
|

NCDs in Nepal: Burgeoning Burden amid Low Priority and the Ways Forward

Abstract: DOI: http://dx.doi.org/10.3126/hprospect.v11i0.7420Health Prospect 2012 Vol.11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“… 4-7 Compared to increased disease burden, CVDs receive disproportionately less attention and resources in Nepalese health systems. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4-7 Compared to increased disease burden, CVDs receive disproportionately less attention and resources in Nepalese health systems. 8 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Compared to increased disease burden, CVDs receive disproportionately less attention and resources in Nepalese health systems. 8 Perceived self-efficacy is defined as people's perceptions about their potential to perform an activity that influences over events that have an impact on their lives. According to Bandura's definition, individuals' expectations or their belief for success or failure to perform a task will determine their outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The Government of Nepal’s commitment toward the Sustainable Development Goals and the National Health Policy 2014 are the recent policy directives to focus on the prevention and control of NCDs in the country. 15 Similarly, the Government of Nepal, in alignment with the Global commitment for 25% relative reduction in premature mortality from NCDs by 2025, 16 has drafted the Multisectoral Action Plan for the Prevention and Control of NCDs (2014–2020). Along with this the Ministry of Health is currently working to restructure health governance, draft a new health policy and design province based health care delivery system for the new Federal Structure of the country.…”
Section: Introductionmentioning
confidence: 99%
“…33 The trend analysis of the metabolic risk factors in Nepal between 1980 and 2008 illustrates high blood pressure, body mass index and blood glucose level as major risk factors for diabetes. 33 A survey showed that a family history of diabetes was present in about one-third of the patients. The highest prevalence of diabetes was seen among the elderly (25.9%).…”
Section: Diabetes and Its Risk Factors In Nepalmentioning
confidence: 99%